THE LOCAL AND EXPATRIATE LEADERSHIP STYLES IN THE IN INDONESIAN COMPANIES: A QUALITATIVE FINDING - Ferryal Abadi; Didin Hikmah Perkasa (Journal of Leadership in Organizations, 2020)
A leader is a crucial factor in the life of an organization. The progress of an organization depends on the extent to which the leader can bring the organization to achieve organizational goals. What emerges is the quality of foreign workers (expatriates). Many expatriates have quality and competences under local workers.  The aim of this study is to know and analyze the problem of foreign workers, whether they are capable of working in accordance with competence since many positions as expatriates occupy leaders or managers. The research method uses a qualitative approach with respondents of local workers who have ever been led by expatriates and locals. The approach used in this study is a qualitative approach; the sampling method uses purposive sampling. The result of this study reveals that local leaders are more effective (than expatriate ones) due to the same culture and language. Expatriate leaders and local leaders have a different working culture that is brought from their own country so that they have their strengths and weaknesses resulted from their leadership style or the way they lead their subordinates.